Aura in temporal lobe epilepsy: clinical and electroencephalographic correlation. - Gupta, A K (1983)
Patients with temporal lobe epilepsy were evaluated for their aura and the site of EEG abnormality. Autonomic and psychic auras were more frequently associated with right-sided temporal lobe lesions in 290 patients.